Relationship of Psychological Well-Being With Perceived Stress, Coping Styles, and Social Support Amongst University Undergraduates - Annette, Ananthi Arulrajah (2000)
The psychological well-being of undergraduates in Malaysia in relation to their perceived stress, coping styles, and social support has not been thoroughly investigated. The aims of the study are (a) to explore the level of psychological well-being, perceived stress, coping styles, and social support; (b) to get an accurate description of the demographic variables; (c) to explore the relationships between psychological well-being, perceived stress, coping styles, and social support; (d) to explore the relationships between psychological well-being, perceived stress, coping styles, and social support after controlling for the possible intervening (demographic) variables; and (e) to explore the differences in psychological well-being, perceived stress, coping styles, and social support with reference to gender, status of learner, and religiosity each in its turn. A random stratified cluster sample of 422 from the faculty of Educational Studies was taken, as a representative of undergraduates in that particular faculty in Universiti Putra Malaysia. The sample came from each of the six programmes in the faculty - the Physical Education programme, the Agricultural Sciences programme, Teaching English As A Second Language programme, Guidance And Counseling programme, the Home Sciences programme, and Teaching Malay As A First Language programme.